Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
A)
-5x²+2x=0
x (-5x+2) = 0
x = 0 lub -5x+2 = 0
-5x = -2
x = 2/5
Odpowiedź: x = 0 lub x = 2/5
B)
6x² = 24x
6x² - 24x = 0
6x (x-4) = 0
6x = 0 lub x-4 = 0
x = 0 lub x = 4
Odpowiedź: x = 0 lub x = 4
C)
x (x-3) = 9x (x-3)
x (x-3) - 9x (x-3) = 0
(x-9x) (x-3) = 0
-8x (x-3) = 0
-8x = 0 lub x-3 = 0
x = 0 lub x = 3
Odpowiedź: x = 0 lub x = 3
Odpowiedź:
A) -5x²+2x = 0
x²( - 5x+2)=0
x²=0 - 5x+2=0
x=0 - 5x= - 2 /:( - 5)
x=2/5=0,4
B) 6x² = 24x /:6
x² =4x
x² - 4x=0
x(x - 4)=0
x=0 x - 4=0
x=4
C) x(x-3)=9x(x-3)
x² - 3x=9x² - 27x
x² - 9x² - 3x+27x=0
- 8x²+24x=0 /:( - 8)
x² - 3x=0
x(x - 3)=0
x=0 x - 3=0
x=3
Szczegółowe wyjaśnienie: